Optimalisasi Perilaku Hidup Bersih dan Sehat di Kp. Kadu Gede RT 02 & 05 Desa Cilember - Sunanda; Eca Apriani; Siti Wulan Sari; Mulyanti; Chikal Fasha; Novita K; Muhnadin; M. Reza Ananda G (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2025)
Clean and Healthy Living Behavior is an important part of efforts to improve the quality of public health. This community service activity aims to raise awareness among residents of Kampung Kadu Gede RT 02 & 05, Cilember Village, about implementing Clean and Healthy Living Behavior, particularly in waste management. The methods used in this activity include education on Clean and Healthy Living Behavior, providing environmentally friendly waste bins, and environmental cleanup activities. The results of the activity show an increase in residents' awareness of disposing of waste properly and maintaining environmental cleanliness.